Economic geographies circuits, flows and spaces - Hudson, Ray 1948- (SAGE, 2005)
Integrating ideas of structure, agency and practice this volume provides a detailed overview of recent key debates in economic geography and a discussion of the economy in terms of circuits flows, and spaces that systematically relates the material to the cultural.